Comparative Studies of the Use of Management Accounting Information - Ewelina Zarzycka (Emerging Markets Journal, 2018)
The paper uses the phenomenon of isomorphism to present the similarities and differences in the use of management accounting information by managers in Poland and Romania. In order to analyze the set of data obtained from the conducted survey, cluster analysis and descriptive statistics have been applied. The studied managers use mainly management accounting information for planning and control tasks (budgeting) and less for formulating strategy and decision making. In their work, they rather apply financial data than nonfinancial indicators. The findings confirm that management accounting in both countries is strongly influenced by the mechanisms of coercive, normative and mimetic isomorphism connected with their specific economic and political development.